Når faller eldre? En kvantitativ undersøkelse bygd på data fra SOS Internasjonale Trygghetssentral - Ottesen, Anneli; Gylløw, Kjersti; Ytrehus, Siri (Nordisk tidsskrift for helseforskning, 2016)
When do the elderly fall? A quantitative study based on data from the SOS Security Alarm CentreFalls are a strain for the elderly and expensive for society. The purpose of this study is to gain knowledge about the extent and variations in falls among home-dwelling elderly throughout the day, the week and the seasons for men and women and different age groups. Data about falls are collected from “SOS International Trygghetssentralen” in connection with safety alarm activation and response All responses to falls in January, February, June and July 2013 in Oslo to persons 76 years and older with a safety alarm is studied, total 1548 falls. Most falls were registered on Mondays and during the winter months. As much as 36 percent of all fallen happens at night between 23 pm and 8 am. This result differs from other studies. The cause of this is unknown. There is a great need for research on the causes of the high incidence falls at night.
Keywords: falls; home-dwelling elderly; risk factors for falls; fall; hjemmeboende eldre; risikofaktorer for fall